The invention of Peter : apostolic discourse and papal authority in late antiquity - Demacopoulos, George E. (Divinations., 2013)
By emphasizing the ways the Bishops of Rome first leveraged the cult of St. Peter to their advantage, George E. Demacopoulos constructs an alternate account of papal history that challenges the dominant narrative of an inevitable and unbroken rise in papal power from late antiquity through the Middle Ages.